AB0117 NK cells isolated from synovial fluid amplify the inflammatory response of fibroblast-like synoviocytes. (23rd January 2014) - Scanu, A.; Oliviero, F.; Mavilio, D.; Sfriso, P.; Punzi, L.
Abstract : Background: Natural killer (NK) cells represent one of the major components of innate immune system and are very important in both early and chronic phases of inflammatory responses. NK cells might contribute to the disease onset through the release of great amount of pro-inflammatory cytokines and through a direct cytolitic activity. However, the role of NK cells in joint inflammation remains unclear. Objectives: To determine whether NK cells are present in synovial fluid (SF) and whether they might play a role in amplifying the inflammatory process. Methods: Mononuclear cells were isolated by density gradient centrifugation from SF collected by arthrocentesis from the knees of 4 untreated patients with inflammatory arthritis (3 seronegative spondiloarthritis and 1 psoriatic arthritis). NK cells were isolated from mononuclear cells by negative immunomagnetic selection. Human fibroblast-like synoviocytes (FLS) were obtained by synovial tissue explants from patients with OA and cocultured for 24 h at 10×10 3 cells/well in 96-well plates with increasing ratios of NK cells (1:1; 1:2; 1:5; 1:10; 1:20). FLS or NK cells were cultured alone as control. Culture supernatants were tested by ELISA for the production of IL-1β, IL-8, CCL2 and TGFβ1. Results: NK cells were isolated from all 4 SF collected. The percentage of NK cells in mononuclear cells was 0.14 in SF1, 0.16 in SF2, 1.06 in SF3 and 0.56 in SF4. IL-1β and TGFβ1 were not detectable in all culture supernatants. When FLS were cocultured with NK cells the production of IL-8 and CCL2 increased in a NK ratio-dependent manner. FLS or NK alone did not release significant levels of IL-8 and CCL2. Conclusions: This study confirms that NK cells are also present in synovial fluid and they might potentially contribute to amplification of the inflammatory process within the joint. The increased cytokine production might be due to the capacity of NK cells to produce fibroblast-activating factors or to direct interactions with synovial cells. Disclosure of Interest: None Declared